Cognitive Analysis of Morphological Phenomena in The Uzbek Language (In Associative-Verbal Aspect) - Umidjon Yigitaliyev (Research Parks Publishers, 2021)
In the article was analyzed the problem of associative-verbal expression in the example of the concept of lingua-grammatical properties of morphological phenomena